2000
DOI: 10.1007/s001270050004
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal depression - myth and reality: maternal depression before and after the birth of a child

Abstract: Background: Much has been written about postnatal depression as a clinical condition. There is some evidence to suggest that a substantial proportion of women who give birth experience a depression in the postnatal period. This paper reports the results of a longitudinal study of the mental health of a large sample of women who were in the early stages of pregnancy at entry to the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(71 citation statements)
references
References 38 publications
3
64
0
4
Order By: Relevance
“…The DSSI contains two 7-item subscales measuring depression and anxiety that have been found to correlate strongly with other scales of depression including the Beck Depression Inventory [25].…”
Section: Potential Confoundersmentioning
confidence: 99%
“…The DSSI contains two 7-item subscales measuring depression and anxiety that have been found to correlate strongly with other scales of depression including the Beck Depression Inventory [25].…”
Section: Potential Confoundersmentioning
confidence: 99%
“…The DSSI was developed by clinicians and validated against a clinical sample (Bedford and Foulds, 1977). It contains two 7-item subscales measuring depression and anxiety, which have been found to correlate strongly with other scales of depression including the Beck Depression Inventory (Najman et al, 2000). Bedford and Foulds and others found that a cut-off of 4 or more symptoms produced the optimum combination of false positives and false negatives, based on Bedford and Foulds' validation studies ( [Bedford and Foulds, 1977] and [Rubino et al, 1997]).…”
Section: Confounders and Mediatorsmentioning
confidence: 99%
“…More recent studies also suggest the DSSI/ SAD is valid for detecting major depressive episodes (Rubino et al 1997). The instrument correlates well and shares items with other measures of depression and anxiety, such as the Edinburgh Postnatal Depression Scale (EPDS) and the Hospital Anxiety/Depression Scale (HADS) (Najman et al 2000). The DSSI/SAD shares with other self-report measures the disadvantage of not detecting less severe episodes.…”
Section: Measurementsmentioning
confidence: 99%